Defense Mechanism Of John Ottway In Carnahan's The Grey Movie (2011): A Psychoanalytic Approach - Saputra, Andhika Cahya; , Drs. Abdillah Nugroho, M.Hum; , Drs. Sigit Haryanto, M. Hum (2013)
The film is one of literary works as a development of drama and novel. The major issue of this study is how the self defense of John Ottway reflected in Carnahan's The Grey movie. The objective of this study is to analyze the film based on the structural elements and to analyze the film based on psychoanalytic approach.The research is qualitative study. The researcher uses two data sources: primary data source and secondary data source. The results of the study show; first the structural elements of the movie are a unity and cannot be separated with each other.